MANAJEMEN PEMBELAJARAN DI PONDOK PESANTREN PEMBANGUNAN MIFTAHUL HUDA MAJENANG KABUPATEN CILACAP - Mahfud, Muntaha (Penerbit CV Tentrem Karya Nusa, 2019)
Islamic boarding school is as a religious education institution. It is supported by a set ofcurriculum that acts as a motivator in teaching and learning. In general, the curriculum used on it isbeing the reference of certain learning, and manifested in the form of determining certain yellowbooks in accordance with the level of knowledge of students by usingmastery learning model. Thisstudy has three objectives: 1) learning management on aspects of planning, implementation andassessment; 2) obstacles in the implementation of learning; and 3) solutions undertaken toovercome obstacles in yellow book study at Pondok Pesantren Miftahul Huda PembangunanMajenang Cilacap. The findings related to learning management at Pondok PesantrenPembangunan Miftahul Huda Majenang are: 1) every early year of caregiver lessons and ustadz(the term address for islam teachers)plan the learning activities by setting learning schedule;2)teaching schedule is made by the principle of deliberation,and involving all people of pesantren; 3)the implementation of learning is done on a predetermined schedule; 4) the assessment of learningas a benchmark of success has not been done comprehensively and routinely.The whole learningmanagement which is held at Pondok Pesantren Pembangunan Miftahul Huda Majenang runsoptimally.Key Words: management, learning, islamic boarding school